How to Know about diplomatic communication in letter-writing of Malay Sultanate? - Muhammad, S. J. N; Rahman, N. S. A (Siauliai University, 2022)
Diplomatic communication is verbal and written speech being used in establishing international relations. Oftentimes, the letter has been employed as a means in diplomatic communication for its simple nature in bearing the loaded messages intended to be delivered to the recipients. It is to note that Malay rulers have been using this form of communication in most of their official government affairs. Therefore, this study is aimed to identify and analyze knowledge diplomatic communication Islam in the letter-writing of Perlis Malay Sultanate. Library search and textual analysis were employed as the data collection methods and subsequently utilized to enumerate the findings of this study. The findings highlighted that the use of eulogistic words and linguistic decorum in letter-writing, as well as present-giving, are among the traditional forms of diplomatic communication practiced by the Perlis Malay Sultanate. These findings are found to be informative to political scientists, historians, or other related diplomatic institutions in approaching letter-writing as the primary means of diplomatic communication between governments.